2009
DOI: 10.1097/tp.0b013e3181af1f53
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Glucose and Glycosylated Hemoglobin in the Screening for Diabetes Mellitus After Renal Transplantation

Abstract: We conclude that patients with an fPG between 5.3 and 6.9 mmol/L or HbA1c more than or equal to 5.8%, alternatively an fPG more than or equal to 5.0 mmol/L combined with HbA1c more than or equal to 5.7% in the early posttransplant period should undergo an OGTT for diagnostic verification of PTDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 93 publications
2
99
2
1
Order By: Relevance
“…It has previously been found that patients with PTDM in general are characterized with a more or less normal FPG with an isolated postprandial hyperglycemia (25). This is in contrast to patients with type 2 diabetes, who tend to have a better correlation between FPG and postprandial hyperglycemia (26).…”
Section: Discussioncontrasting
confidence: 43%
“…It has previously been found that patients with PTDM in general are characterized with a more or less normal FPG with an isolated postprandial hyperglycemia (25). This is in contrast to patients with type 2 diabetes, who tend to have a better correlation between FPG and postprandial hyperglycemia (26).…”
Section: Discussioncontrasting
confidence: 43%
“…The recommended approach also suggests performing the OGTT in a large number of patients, making it time-consuming and costly in clinical practice. To select patients for a diagnostic OGTT, screening strategies based on FPG or glycated hemoglobin (HbA 1c ) have been proposed for patients who have undergone transplantation (11)(12)(13) and the general population (14); no such approach has been explored in KTx candidates.…”
mentioning
confidence: 99%
“…The incidence of NODAT may be increased as a consequence of the combination of multiple risk factors. Valderhang et al have found that the incidence of NODAT was 14% (14). Several authors have shown that the most important risk factors of NODAT are immunosuppressive drugs, but family history, weight, and BMI of the recipient are also essential (3,4,6,15,16).…”
Section: Discussionmentioning
confidence: 99%